Spatio-temporal wide-field imaging with 50 fs resolution based on frequency upconversion - Kimbaras, Džiugas; Kling, Matthias F.; Butkus, Rytis; Wnuk, Pawel (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Time resolved imaging is a powerful tool of collecting spatial, temporal and spectral data of various high-speed phenomena. Being beneficial to a number of different fields ranging from biology, medicine, industry to fundamental research, various imaging techniques are constantly being developed, each presenting unique research and various advantages and disadvantages. We present a high-speed imaging method, which employs a non-collinear sum frequency generation based optical shutter [1] together with wide-field imaging module. The main idea is described as following: the object plane of some repetitive light scattering, emission or reflection event is imaged on the non-linear crystal and gated by a short laser pulse. By changing the delay of the gating pulse, multiple snapshots carrying spatial and spectral data of the event are upconverted and recorded. Afterwards, the event can be recreated with femtosecond temporal resolution, limited by the duration of the gating pulse.
CRIS-Team Scopus Importer:2023-04-20